PENERAPAN MODEL PEMBELAJARAN PENEMUAN TERBIMBING PADA MATA PELAJARAN MATEMATIKA UNTUK MENINGKATKAN PRESTASI BELAJAR SISWA SMP - Theresiana Lukiana; Mega Irhamna (Jurnal Dedikasi Pendidikan, 2021)
This study aims to determine whether the guided discovery learning model on the Pythagorean theorem material can improve student learning outcomes for Class VIII-7 SMP Negeri 2 Deli Tua District. The object of this research is all students of Class VIII-7 SMP Negeri 2 Deli Tua District, totaling 32 students. This research is a classroom action research which consists of two cycles. The implementation of this research consists of four stages, namely planning, action, observation and reflection. Data was collected through a written test in the form of multiple choices given at the end of the lesson. The results of data analysis showed that student learning outcomes on the Pythagorean theorem material taught by the application of the guided discovery learning model increased in each cycle. The results of the learning evaluation in the first cycle reached an average of 63.50 and while in the second cycle by applying the Make A Match Model learning strategy increased in the second cycle the average value increased to 86.85. So it can be concluded that the guided discovery learning model can improve student learning outcomes in class VIII-7 SMP Negeri 2 Deli Tua.